Correlates for the severity of suicidal risk in participants with common mental disorders with comorbid chronic medical conditions in rural primary healthcare settings in India - Johnson-Pradeep Ruben; Maria L. Ekstrand; Elsa Heylen; Krishnamachari Srinivasan (Indian Journal of Psychiatry)
Context: Suicide is on the rise in low- and middle-income countries (LMICs), including India. There are limited studies assessing factors linked to the severity of suicidal risk in patients with depression and comorbid chronic medical disorders in primary healthcare (PHC) settings. Aim: This study examines factors linked to suicidal risk among participants in a cluster randomized controlled trial of collaborative care intervention (Healthier Options through Empowerment (HOPE Study)). Settings and Design: The setting was at 49 PHC in the rural Ramanagara District of Karnataka State in southern India. Study eligibility criteria included being ≥30 years with at least mild depression or generalized anxiety disorder and at least one medical condition (cardiovascular disorder or type 2 diabetes mellitus). Methods and Material: The severity of suicidal risk at baseline was assessed using the Mini International Neuropsychiatric Interview (MINI), and other measures included the severity of depression (Patient Health Questionnaire-9-items (PHQ-9)), the severity of anxiety (Generalized Anxiety Disorder Scale-7-items (GAD-7)), disability, social support, quality of life, number of comorbid chronic medical illnesses, and body mass index (BMI). Statistical Analysis Used: Chi-square tests and independent-samples t-tests were used to compare the demographic and clinical characteristics of the no-low and mod-high suicidal risk groups. Logistic regression analysis was used to identify correlates associated with the mod-high suicidal risk group. Results: Mod-high suicidal risk was significantly positively associated with the severity of depression and disability and significantly negatively associated with social support. Conclusion: The severity of depression, higher disability scores, and lower social support were found to be independent correlates of mod-high suicidal risk. Screening, managing depression, and facilitating social support for patients with chronic medical illness in PHC settings may reduce suicidal risk.